Hydrothermal pretreatment of Eucalyptus by-product and refining of xylooligosaccharides from hemicellulosic hydrolysate - Aline Otaviano, Cecília [UNESP]; Ussemane Mussagy, Cassamo; Roberto Paz-Cedeno, Fernando [UNESP]; Fernando Brandão Pereira, Jorge; Masarin, Fernando [UNESP] (Elsevier, 2023)
Xylooligosaccharides (XOS) are highly effective food bioproducts of value to the prebiotic market. The use of hydrothermal pretreatment (HP) on Eucalyptus by-product (EB) under suitable conditions can allow to obtain valuable XOS-rich hemicellulosic hydrolysate (HH). This work aimed to design an efficient methodology to refine XOS-rich HH, boosting the development of new applications for natural XOS obtained from EB. The approach includes the refining of XOS-rich HH, obtained after the HP, in which the HH was separated and fractioned using a liquid–liquid extraction (LLE) process with organic solvents, a vacuum evaporation, and an integrated downstream processing using the two operations. Both refining processes were efficient in removing unwanted components from HH, mainly total aromatics, including hydroxymethylfurfural (HMF) and furfural. LLE performance was maximized by adjusting the volumetric ratio of ethyl acetate (EtOAc). This operation was highly efficient for removing the aromatic fraction, with a removal efficiency of 63–82% of the total aromatics and only a small loss of XOS (of circa 15%). The use of vacuum evaporation to refine the HH allowed to remove 55.4% of total aromatics with an XOS average loss of 23.8%. The combination of vacuum evaporation and LLE (1:1 vol ratio of HH: EtOAc) was beneficial for the removal of total aromatics (75.7%), but negatively affected the content of XOS in the refined HH (average loss of XOS of 29.3%). Anyway, the integrated platform resulted in a purification index of 75.5%, which represents an increase of 34.1% when compared to raw HH. This work demonstrated that the use of LLE using EtOAc, vacuum evaporation and an integrated processing using both operations are effective and simple approaches to refine XOS-rich HH, especially for the removal of aromatics contaminants, presenting a potential to improve the industrial hemicellulose biorefining processes.
Keywords: Aromatics removal; Liquid-liquid extraction; Refining; Vacuum evaporation; Xylooligosaccharides